2020
DOI: 10.3390/cells9061526
|View full text |Cite
|
Sign up to set email alerts
|

Role of Elevated Intracellular S-Adenosylhomocysteine in the Pathogenesis of Alcohol-Related Liver Disease

Abstract: Background: The earliest manifestation of alcohol-related liver disease (ALD) is steatosis, characterized by the accumulation of lipid droplets (LDs) in hepatocytes. Findings from our laboratory have indicated that many pathological changes, including steatosis, correlate with the alcohol-induced hepatocellular increases in S-adenosylhomocysteine (SAH). Based on these considerations, we hypothesized that an experimental increase in intracellular SAH alone will result in similar steatotic changes to those seen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 60 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…The earliest manifestation of alcohol-related liver disease is steatosis, which is characterized by the accumulation of lipid droplets in liver cells. Arumugam et al ( 25 ) demonstrated that many pathological changes, including steatosis, are associated with the alcohol-induced increase in SAH hepatocytes. A study that investigated the impaired Hcy metabolism in patients with alcohol-related liver disease from Taiwan ( 26 ) showed that impaired Hcy metabolism may disrupt antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…The earliest manifestation of alcohol-related liver disease is steatosis, which is characterized by the accumulation of lipid droplets in liver cells. Arumugam et al ( 25 ) demonstrated that many pathological changes, including steatosis, are associated with the alcohol-induced increase in SAH hepatocytes. A study that investigated the impaired Hcy metabolism in patients with alcohol-related liver disease from Taiwan ( 26 ) showed that impaired Hcy metabolism may disrupt antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…Fully differentiated 3T3-L1 adipocytes grown on coverslips were treated with different concentrations of DZA for 48 h. The processing for immunofluorescent staining was done as detailed in our previous publication 15 . Briefly, coverslips were rinsed with PBS and fixed with 4% paraformaldehyde followed by background quenching with 50 mM NH 4 Cl in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated from control and DZA-treated 3T3-L1 adipocytes as detailed previously 15 using PureLink RNA Mini Kit according to the manufacturer’s instructions. The concentration of the RNA and 260/280 nm optical density (OD) ratio was determined spectrophotometrically (NanoDrop Technologies, Wilmington, DE).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [ 149 , 150 , 151 ] Arumugam et al revealed in their study that increased intracellular SAH is sufficient to promote fat accumulation in hepatocytes, which resembles that seen after alcohol exposure [ 152 ]. Moreover, PRMT1 serves the role of transcriptional coactivator, participating in splicing and upstream of signal transduction [ 153 , 154 , 155 , 156 , 157 , 158 , 159 , 160 ].…”
Section: Hepatocyte Prmt1 and Oxidative Stressmentioning
confidence: 99%